2023
DOI: 10.1111/jace.19152
|View full text |Cite
|
Sign up to set email alerts
|

Field strength effect on elastoplastic behavior of aluminoborosilicate glass: II. Volumetric recovery

Abstract: The field strength (FS) effect of six different network modifiers on the elastoplastic properties of aluminoborosilicate glasses was explored using a volumetric recovery study. This work, in conjunction with Part I, explored the intersection of hardness, crack resistance, and other physical properties with glass elasticity. Results showed that (1) the elastic volume fraction decreased with FS for both the alkali and alkaline earth (AE) glasses; (2) the Poisson's ratio did not trend with pile‐up or shear flow v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…13 Regardless, the connectivity of a glass network is intimately related to mechanical properties of a glass, adapting under both thermal and mechanical stresses. 14 Previous work has found that hardness, crack resistance, 15 elastic moduli, 16 and plasticity 17 have all increased as modifier FS was increased in the current ABS compositions. It was posited that the observed increase in hardness and elastic moduli as a function of increasing NWM-FS was due to increased atomic packing density (decreased molar volume) as a result of increased NWM-oxygen bond strength (i.e., shortened NWM-O bond length).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…13 Regardless, the connectivity of a glass network is intimately related to mechanical properties of a glass, adapting under both thermal and mechanical stresses. 14 Previous work has found that hardness, crack resistance, 15 elastic moduli, 16 and plasticity 17 have all increased as modifier FS was increased in the current ABS compositions. It was posited that the observed increase in hardness and elastic moduli as a function of increasing NWM-FS was due to increased atomic packing density (decreased molar volume) as a result of increased NWM-oxygen bond strength (i.e., shortened NWM-O bond length).…”
Section: Introductionmentioning
confidence: 85%
“…The same batch compositions (in mole percent), as well as melting and annealing temperatures, were used to synthesize all AE-ABS glasses for the current and previous studies. More details regarding glass design and synthesis are given in the previous work, [15][16][17] and more material properties are provided in Appendix A.…”
Section: Synthesis and Preliminary Characterizationmentioning
confidence: 99%
See 3 more Smart Citations